Distribution of Serum IgG Subclass Antibodies to Porphyromonas gingivalis in Periodontitis Patients - SAKAI, Yoko; ITO, Hiro-o; OKADA, Hiroshi (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1994)
The present study was conducted to investigate the responses of serum IgG subclass antibodies against Porphyromonas gingivalis and immunodominant antigens of the organism for the different IgG subclasses. Sera were obtained from patients with adult periodontitis (AP), after assessing pocket probing depth from 6 sites per tooth and a full set of intraoral radiographs at the initial examination. Enzyme-linked immunosorbent assay for IgG subclass antibodies against whole cells of P. gingivalis strain 381 in 28 periodontitis patients and 14 periodontally healthy controls revealed that all 4 subclasses and total IgG anti-P. gingivalis levels were significantly higher in the cases (P<0.0001, by Mann-Whitney U test) than those in healthy controls. IgG subclass distribution patterns varied among the patients. Antibody levels of total IgG, IgG 1, IgG 3 and IgG 4 did not correlate with any clinical parameters. However, IgG 2 titer correlated positively with mean pocket probing depth and rate of periodontally affected teeth that exhibited more than 30% bone-loss on the radiographs. Specificities of different IgG subclasses in 25 patients and 14 control subjects were examined by Western blot analysis against sonic extracts of the organism. P. gingivalis reactive IgG 2 was found in 22/25 patients and 4/14 controls, while IgG 1 responses were found in all patients and healthy controls. An antigen displaying a smeared pattern at 50-100 kDa was immunodominant for IgG 2. Only 3/25 of AP patients and 1/14 controls showed a positive reaction in IgG 3, 5/25 of patients and no control subject were positive for IgG 4. The significance of IgG 2 responses in the periodontitis patients suggests the importance of carbohydrate antigens of P. gingivalis in periodontal infection.